The Efg1-Bud22 dimer associates with the U14 snoRNP contacting the 5′ rRNA domain of an early 90S pre-ribosomal particle - Beine-Golovchuk, Olga; Kallas, Martina; Kunze, Ruth; Griesel, Sabine; Baßler, Jochen (Nucleic acids research, 2024)
The DEAD-box helicase Dbp4 plays an essential role during the early assembly of the 40S ribosome, which is only poorly understood to date. By applying the yeast two-hybrid method and biochemical approaches, we discovered that Dbp4 interacts with the Efg1-Bud22 dimer. Both factors associate with early pre-90S particles and smaller complexes, each characterized by a high presence of the U14 snoRNA. A crosslink analysis of Bud22 revealed its contact to the U14 snoRNA and the 5 ' domain of the nascent 18S rRNA, close to its U14 snoRNA hybridization site. Moreover, depletion of Bud22 or Efg1 specifically affects U14 snoRNA association with pre-ribosomal complexes. Accordingly, we concluded that the role of the Efg1-Bud22 dimer is linked to the U14 snoRNA function on early 90S ribosome intermediates chaperoning the 5 ' domain of the nascent 18S rRNA. The successful rRNA folding of the 5 ' domain and the release of Efg1, Bud22, Dpb4, U14 snoRNA and associated snoRNP factors allows the subsequent recruitment of the Kre33-Bfr2-Enp2-Lcp5 module towards the 90S pre-ribosome. Graphical Abstract